STRENGTHENING EARLY CHILDHOOD TEACHER SERVICES IN CREATIVITY TO MAKE INSPIRATIONAL EDUCATIONAL TOOLS - Afriyane Ismandela; Dinda Fatma Nabila; Retno Wulandari; Abdul Halif; Paramita Rusadi; Nini Saputri; Widya Putri; Jhoni Warmansyah (Fakultas Sains dan Teknologi, 2023)
Improving the quality of PAUD teacher services is essential in developing creativity and inspiring educational aids. The Participatory Action Research (PAR) technique is used to improve PAUD teacher services by encouraging creativity and producing educational teaching aids that are inspiring through Community Service (PKM). PKM begins with a collaborative planning phase with PAUD teachers and other relevant stakeholders. The PKM team engages teachers in workshops and meetings to identify needs and actively participates in training sessions, hands-on activities, and reflection sessions during implementation. They are encouraged to try new techniques, discuss their experiences, and work together to overcome problems and obstacles that arise along the way. The Joint Community Service team provides ongoing support and direction, fostering a collaborative and empowered atmosphere where instructors can leverage their creativity and build engaging instructional resources. The impact of the Joint Community Service was evaluated using a variety of data collection approaches, including surveys, observations, interviews, and recordings of the instructor's creative practices and the resulting pedagogical materials. These findings indicate that the self-confidence, knowledge, and abilities of PAUD teachers significantly increase in designing and making educational teaching aids that are inspiring. This study generates a sense of ownership, empowerment, and continued professional growth by integrating PAUD teachers as active participants and research partners. It also makes it easier for participating teachers and the more prominent early childhood education community to disseminate and share best practices. These findings can help educators, researchers, and policymakers create and implement collaborative, context-appropriate interventions to enhance teacher creativity in early childhood education. Keywords: Early Childhood Teacher, Creativity, Inspirative Educational Tools